Calochroa miroklichai sp. nov., a new species from Thailand with rectification of different concepts of Calochroa tritoma (Schmidt-Goebel) and comparisons to similar species. (Coleoptera: Cicindelidae) - Moravec, Jiří; Dheurle, Charles; Wiesner, Jürgen (Zootaxa, 2023)
A new species of the genus Calochroa Hope, 1838 is described as new to science from Thailand. Two different concepts of Calochroa tritoma (Schmidt-Goebel, 1846) are rectified here, stating that the correct concept of C. tritoma (fully corresponding to the holotype in NMPC) is that presented by Naviaux (1991), Naviaux & Pinratana (2004) and Klícha & Ďuríček (2021), while C. tritoma sensu Pearson et al. (2020) is described here as Calochroa miroklichai sp. nov. Accordingly, C. tritoma sensu Acciavatti & Pearson (1989) represents a different, probably an undescribed species. C. anometallescens (W. Horn, 1893) and Calochroa laurae (Gestro, 1893), as well as the new species, have been partly misidentified as C. tritoma in collections. The occurrence of C. tritoma is newly restricted to Thailand and Myanmar only. The above-mentioned species, as well as Calochroa fumikoae Wiesner & Phyu, 2019 are compared to C. miroklichai sp. nov. Calochroa goebeli (W. Horn, 1895), treated in literature either as a “variety” or junior synonym of C. anometallescens (or confused with C. tritoma), proved to represent a separate species. Some other taxa and discrepancies within the genus are discussed. Habitats and characters of several species versus their relations to the genus Cosmodela Rivalier, 1961 also are annotated. Habitus and diagnostic characters are illustrated in colour photographs, and photographs of the habitus and labels of type specimens of C. tritoma, C. laurae and C. goebeli are presented here for the first time.